2017
DOI: 10.4314/jab.v109i1.4
|View full text |Cite
|
Sign up to set email alerts
|

<i>Garcinia lucida</i> Vesque (Clusiaceae): from traditional uses to pharmacopeic monograph for an emerging local plant-based drug development

Abstract: Guedje et al., J. Appl. Biosci. 2017 Garcinia lucida Vesque (Clusiaceae): from traditional uses to pharmacopeic monograph for an emerging local plant-based drug development 10594Journal of Applied Biosciences 109: 10594-10608 ISSN 1997-5902 Garcinia lucida Vesque (Clusiaceae): from traditional uses to pharmacopeic monograph for an emerging local plant-based drug development ABSTRACT Objectives: This paper seeks to assess information on the identity, traditional uses, safety and efficacy of Garcinia lucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…However, there were some gaps and discrepancies between the two types of knowledge, most notably with the fact that harvesters identified two types of "essok" based on the ability of bark to be more or less easily removed from wood. In fact, this information has later led to found that there exists only one species of G. lucida, accurately identified by trained botanists (Guedje et al, 2017), from which, bark was easily removed from wood like "cassava peel" when trees were characterized physiologically by the existence or predominance of an upward sap flow, due to good water supply in trees and consequently on soil, given the fact that the species was mainly found in hilly mountain sides. On the contrary, bark was hardly removed when trees were characterized by the predominance of a downward sap flow (Guedje et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were some gaps and discrepancies between the two types of knowledge, most notably with the fact that harvesters identified two types of "essok" based on the ability of bark to be more or less easily removed from wood. In fact, this information has later led to found that there exists only one species of G. lucida, accurately identified by trained botanists (Guedje et al, 2017), from which, bark was easily removed from wood like "cassava peel" when trees were characterized physiologically by the existence or predominance of an upward sap flow, due to good water supply in trees and consequently on soil, given the fact that the species was mainly found in hilly mountain sides. On the contrary, bark was hardly removed when trees were characterized by the predominance of a downward sap flow (Guedje et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many active compounds with bioactivities such as antibacterial, antimicrobial, anti-inflammatories, antacids, curare antidote or inhibitory effect, β-lactamase inhibition have been found in its diverse plant parts and summarized by Guedje et al (2017). Several in vitro and in vivo activities were carried out on G. lucida and found to be potential good sources of numerous therapeutic agents (Nguedia and Nsagha, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The natural habitat of G. lucida is the Atlantic "primary" rain forests. G. lucida tree grows in high-density stands covering few hectares with an abundance varying from 348 young matures (5 -10 cm dbh) to 5 large trees (> 20 cm dbh) per hectare (Guedje et al 2017).…”
Section: Description Of Study Speciesmentioning
confidence: 99%
“…The bark is used as an additive to palm wine production and in distilling fermented palm wine to produce liquor. The bark and the seeds, dried or fresh, are widely used for medicinal purposes to prevent food poisoning and to cure stomach and gynaecological pains, as well as to cure snake bites (Guedje, Tadjouteu, Onana, Nnanga Nga, & Ndoye, 2017). This species is a gregarious species that grows in dense stands on the slopes of forests above 500 meters of altitude.…”
Section: Introductionmentioning
confidence: 99%
“…2). The bark and the seeds are widely used in Central and West Africa as additive to palm wine production, and for multiple medicinal purposes against poisoning, gastritis, snakebite, gynaecological pains and infections, sexual diseases and cancers (Guedje et al, 2017). The results from pharmacological studies using diverse plant parts of this species have found it to be potential good sources of numerous therapeutic agents (Nguedia & Nsagha, 2014), and have supported its popular use as antibacterial, antimicrobial, anti-inflammatory, antacids, curare antidote or inhibitory effect, β-lactamase inhibition have been found in its diverse plant parts (Kamanyi et al, 1990;Nyemba et al, 1990;Fotie et al, 2007;Gangoué-Piéboji et al, 2009;Momo et al, 2011;Lacmata et al, 2012).…”
Section: Methodsmentioning
confidence: 99%